FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE TEACHERS OF PHYSICAL EDUCATION AND SPORTS IN THE CONDITIONS OF INCLUSIVE EDUCATION - MATNAZAROV Anvar O'ktamovich («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
The article presents the results of a theoretical study of general approaches and technologies for the forma- tion of readiness of future teachers of physical education and sports to work in the conditions of inclusive education. Inclusion sets a new paradigm of public life, social structure, requires serious transformations of social institutions, processes and practices, implies the achievement of maximum community of each person with other people and society as a whole. Achieving full inclusion of each individual in social life is becom- ing a priority task of modern society, the solution of which is associated with a change in existing stereotypes of public consciousness regarding the features of pedagogical support for students with special educational needs.